Molecular basis for and chemogenetic modulation of comorbidities in GABRG2‐deficient epilepsies. (14th May 2019) - Zhang, Chun‐Qing; McMahon, Bryan; Dong, Huancheng; Warner, Timothy; Shen, Wangzhen; Gallagher, Martin; Macdonald, Robert L.; Kang, Jing‐Qiong
Abstract: Objective: γ‐Aminobutyric acid type A (GABAA ) receptor subunit gene mutations are significant causes of epilepsy, which are often accompanied by various neuropsychiatric comorbidities, but the underlying mechanisms are unclear. It has been suggested that the comorbidities are caused by seizures, as the comorbidities often present in severe epilepsy syndromes. However, findings from both humans and animal models argue against this conclusion. Mutations in the GABAA receptor γ2 subunit gene GABRG2 have been associated with anxiety alone or with severe epilepsy syndromes and comorbid anxiety, suggesting that a core molecular defect gives rise to the phenotypic spectrum. Here, we determined the pathophysiology of comorbid anxiety in GABRG2 loss‐of‐function epilepsy syndromes, identified the central nucleus of the amygdala (CeA) as a primary site for epilepsy comorbid anxiety, and demonstrated a potential rescue of comorbid anxiety via neuromodulation of CeA neurons. Methods: We used brain slice recordings, subcellular fractionation with Western blot, immunohistochemistry, confocal microscopy, and a battery of behavior tests in combination with a chemogenetic approach to characterize anxiety and its underlying mechanisms in a Gabrg2 +/Q390X knockin mouse and a Gabrg2 +/− knockout mouse, each associated with a different epilepsy syndrome. Results: We found that impaired GABAergic neurotransmission in CeA underlies anxiety in epilepsy, which is due to reduced GABAA receptor subunit expression resulting from the mutations. Impaired GABAA receptor expression reduced GABAergic neurotransmission in CeA, but not in basolateral amygdala. Activation or inactivation of inhibitory neurons using a chemogenetic approach in CeA alone modulated anxietylike behaviors. Similarly, pharmacological enhancement of GABAergic signaling via γ2 subunit‐containing receptors relieved the anxiety. Significance: Together, these data demonstrate the molecular basis for a comorbidity of epilepsy, anxiety, and suggest that impaired GABAA receptor function in CeA due to a loss‐of‐function mutation could at least contribute to anxiety. Modulation of CeA neurons could cause or suppress anxiety, suggesting a potential use of CeA neurons as therapeutic targets for treatment of anxiety in addition to traditional pharmacological approaches.